2021
DOI: 10.3390/molecules26195997
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Potential Role of Natural Products to Combat Radiotherapy and Their Future Perspectives

Abstract: Cancer is the second leading cause of death in the world. Chemotherapy and radiotherapy (RT) are the common cancer treatments. In addition to these limitations, the development of adverse effects from chemotherapy and RT reduces the quality of life for cancer patients. Cellular radiosensitivity, or the ability to resist and overcome cell damage caused by ionizing radiation (IR), is directly related to cancer cells’ response to RT. Therefore, radiobiological research is emphasizing chemical compounds ’radiosens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 169 publications
(156 reference statements)
0
12
0
Order By: Relevance
“…For many years, the use of products derived from nature has been of great interest to man, in the preservation of the state of health, for the improvement of physical and mental health, and in the prevention of diseases [ 41 ]. Several studies have reported the radio/chemoprotective role of some natural compounds in combination with radiotherapy and chemotherapy and/or synergistic effects in alleviating complications associated with radiotherapy/chemotherapy and increasing the efficacy of cancer therapies [ 42 ]. In addition, some of them can cross the BBB and this property is one of the main considerations for the development of therapies for the CNS [ 43 ].…”
Section: Natural Compounds In the Therapy Of Gliomamentioning
confidence: 99%
See 1 more Smart Citation
“…For many years, the use of products derived from nature has been of great interest to man, in the preservation of the state of health, for the improvement of physical and mental health, and in the prevention of diseases [ 41 ]. Several studies have reported the radio/chemoprotective role of some natural compounds in combination with radiotherapy and chemotherapy and/or synergistic effects in alleviating complications associated with radiotherapy/chemotherapy and increasing the efficacy of cancer therapies [ 42 ]. In addition, some of them can cross the BBB and this property is one of the main considerations for the development of therapies for the CNS [ 43 ].…”
Section: Natural Compounds In the Therapy Of Gliomamentioning
confidence: 99%
“…RES is also able to act as an antitumor radiosensitizing agent in the colon, prostate, skin, breast cancer, leukemia, hepatoma, and other cancers, including brain tumors [ 42 ]. RES is also a radiation sensitizer in SU-2 (highly radio-resistant) human glioma stem cells.…”
Section: Natural Compounds In the Therapy Of Gliomamentioning
confidence: 99%
“…It has been shown to efficiently inhibit both the influenza virus and SARS-CoV-2. A study discovered that the marine polysaccharide repressed viral replication and lowered viral protein expression in a dose-dependent way ( Akter et al., 2021 ). As the lambda-carrageenan dose was increased from 0 to 300 g/mL, the presence of spike viral proteins on SARS-CoV-2 and influenza A viral proteins dropped drastically ( Zahran et al., 2020 ).…”
Section: Impact Of Marine Natural Products In Covid-19mentioning
confidence: 99%
“…Moreover, for a radiomodulating compound to offer a practical gain in RT, it has to show a differential effect between normal tissues and tumours, as it would be of no avail to use a drug that increases the radiosensitivity of tumours and normal tissues alike, nor would it be therapeutically sound to mitigate radiation-induced damage in the two compartments to the same extent. The general failure of synthetic compounds to act as selective radioprotectors and the difficulty in finding effective radiosensitizers with low normal-tissue toxicity has driven researchers to focus on natural substances with radiomodulating potential and several botanicals, which could be less expensive than synthetic ones, have been screened for their radioprotective or radiosensitizing activity [ 14 , 15 , 16 ]. Plant-derived polyphenols in particular have gained considerable attention in the long-standing quest for intrinsically low-toxic radioprotecting/radiosensitizing drugs [ 12 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, since most of the IR damage arises from the interaction of IR-induced free radicals with biomolecules, natural substances, such as curcumin, chlorogenic acids, and different flavonoids could serve as radioprotectors, being able to combine with or prevent the formation of free radicals [ 18 ]. On the other hand, the anti-cancer activity of natural radiosensitizers has been correlated with their ability to inhibit the intracellular glutathione (GSH) redox buffering metabolism [ 19 ], to abrogate radiation-induced cell-cycle checkpoints that favour damage repair [ 20 ], to downregulate expression of genes implicated in cancer cell proliferation and resistance to radiation-induced apoptosis such as COX-2 [ 21 ], and to counteract tumour progression and migration by inhibiting pro-inflammation nuclear factor kappa B (NF-kB) transcription factor and disrupting a number of signalling pathways implicated in uncontrolled proliferation and enhanced angiogenesis, as reviewed in [ 16 ].…”
Section: Introductionmentioning
confidence: 99%